The Association of Osteosarcopenia With Functional Disability in Community-Dwelling Mexican Adults 50 and Older - López-Teros, Miriam T.; Rosas-Carrasco, Oscar; Sánchez-García, Sergio; Castro-Porras, Lilia; Luna-López, Armando; Agudelo-Botero, Marcela (Frontiers in Medicine, 2021)
Background: Osteosarcopenia (OS) has recently been described as a predictor of negative outcomes in older adults. However, this alteration in body composition has not been widely studied. In Mexico and Latin America, no information is available on its frequency or associated factors. Objective: To analyze the association between OS with FD in community-dwelling Mexican adults 50 and older. Design: Cross-sectional secondary data analysis was performed using primary data from a prospective study Frailty, Dynapenia and Sarcopenia Study in Mexican Adults (FraDySMex). Setting and Participants: Eight hundred and twenty-five people were included, 77.1% women, aged 70.3 ± 10.8 years old. Methods: OS was defined as when the person was diagnosed with sarcopenia (SP) plus osteopenia/osteoporosis. The SP diagnosis was evaluated in accordance with the criteria of the European Working Group for the Definition and Diagnosis of Sarcopenia (EWGSOP), and the osteoporosis diagnosis using World Health Organization (WHO) criteria. Muscle mass and bone mass were evaluated using dual-energy X-ray absorptiometry (DXA). FD was evaluated using the basic activities of daily living (BADL) and the instrumental activities of daily living (IADL). Additional sociodemographic and health co-variables were also included, such as sex, age, education, cognitive status, depression, comorbidity, hospitalization, polypharmacy, urinary incontinence, and nutrition variables such as risk of malnutrition and obesity. Associations between OS with FD were evaluated using multiple logistic regression. Results: The prevalence of OS was 8.9% and that of FD was 8.9%. OS was associated with FD [odds ratio (OR): 1.92; CI 95%: 1.11–3.33]. Conclusions and Implications: Comprehensive OS assessment could help clinicians identify risk factors early, and thus mitigate the impact on FD in older people.